EFL Students’ Preferences toward the Lecturer’s Corrective Feedback in Business Letters Writing - Sanu, La Ode (Dinamika Ilmu, 2016)
This study aimed to investigate; the students’ preferences toward the lecturer’s corrective feedback in the business letter writing and their reasons why they preferred for particular corrective feedback types. A case study was used by involving 15 EFL students who enrolled the Business Correspondence Course. The questionnaire and interview were used as the research instruments. This study revealed that; (1) the students preferred to receive lecturer correction (M=5.00), followed by lecturer-students conferencing (M=4.13), peer-correction (M=2.73), error identification (M=2.00), lecturer commentary (M=1.93), and self-correction (M=1.27). (2) the students’ reasons at choosing the lecturer correction were getting the directly good correction from the lecturer, which it would be used as the reference/guide for further improvements both linguistic accuracy and business letter organization. In lecturer-students conferencing, beside they got good correction and grateful appreciation from both their lecturer and other students, they could learn and share the knowledge of errors made together; however they ashamed their linguistics errors, low ability and knowledge in formatting good business letter could be known by others. In peer-correction, the students got the unsatisfied and satisfied corrective feedback from their peers; and they were doubt with their peers’ ability and knowledge in giving correction. In Error identification and lecturer commentary, it was difficult for the students to diagnose the real errors and to correct them. Finally, the reasons of self-correction were useless and unsatisfied to evaluate their own work since they had limited ability and knowledge in formatting the business letter writing effectively.